Replication Data for: 4-km gridded historical and future scenarios for sea level rise in Honduras - Navarro Racienes, Carlos Eduardo; Monserrate Rojas, Fredy Alexander (International Center for Tropical Agriculture, 2018)
Future sea level rise change scenarios for Honduras were derivate from 10 General Circulation Models (GCMs) of the CMIP5 projections for two Representative Concentration Pathways (RCP’s; RCP 4.5 and 8.5; IPCC, 2013) and the time-series 2006-2100. We resample the projections at 4-km and aggregated into the three future periods named as 2030s (Climatic normal –CN- for 2026 to 2045), 2050s (CN for 2046-2065) and 2080s (CN for 2076 to 2095) as well. The future periods were selected by PNUD and MiAmbiente in Honduras in order to get climatic information for the decision making processes around the climate change in the short, medium and large terms. We used the variable Sea Surface Height bove geoid (zos). We make available two types of data: